Archives Management System Analysis Of Sales Operations Division PT United Tractors - Dinda Mandasari; Christian Wiradendi Wolor; Maulana Amirul Adha (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The aim of this research is to find out how to manage archives starting from creation, utilization, storage, rediscovery, transfer, depreciation and destruction of archives. This research uses qualitative research and 5 informants as research sources. The data collection techniques used are interview techniques, documentation and observation. Data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of research regarding the archive management system at the Sales Operation Division of PT United Tractors include creation, storage and retrieval. The obstacle faced by archivists in managing archives is that archives are not found when they are needed, this is caused by several factors, including: 1) There are no regulations governing the procedures for borrowing archives, 2) Archivists who are not competent in the field of archives. The conclusion of this research is that the records management system in the Sales Operation Division includes the processes of creation, storage and retrieval. The advice given is that the company needs to evaluate archive management procedures at PT United Tractors, and hold training for archivists so that archives can be managed well by archivists.